The Chemokine Receptor CCR7 Uses Distinct Signaling Modules With Biased Functionality to Regulate Dendritic Cells - Rodríguez-Fernández, José Luis; Criado-García, Olga (Frontiers in Immunology, 2020)
Chemotaxis is a molecular mechanism that confers leukocytes the ability to detect gradients of chemoattractants. Chemokine receptors are well known regulators of chemotaxis in leukocytes; however, they can regulate several other activities in these cells. This information has been often neglected, probably due to the paramount role of chemotaxis in the immune system and in biology. Therefore, the experimental data available on the mechanisms used by chemokine receptors to regulate other functions of leukocytes is sparse. The results obtained in the study of the chemokine receptor CCR7 in dendritic cells (DCs) provides interesting information on this issue. CCR7 guides the DCs from the peripheral tissues to the lymph nodes, where these cells control T cell activation. CCR7 can regulate in DCs chemotaxis, survival, migratory speed, cytoarchitecture and endocytosis. Biochemical and functional analyses show: First, that CCR7 uses in DCs the PI3K/Akt pathway to control survival, the MAPK pathway to control chemotaxis and the RhoA pathways to regulate actin dynamics, which in its turn controls migratory speed, cytoarchitecture, and endocytosis; Second, that these three signaling pathways behave as modules with a high degree of independence; Third, that although each one of these routes can regulate several functions in different settings, CCR7 promotes in DCs a functional bias in each pathway. The data uncover an interesting mechanism used by CCR7 to regulate the DCs, entailing multifunctional signaling pathways organized in modules with biased functionality. A similar mechanism could be used by other chemoattractant receptors to regulate the functions of leukocytes.